Topology in the UPTC: the legacy of Professor Manuel Suárez—1941-2020 - Fúneme, Cristian Camilo; Rodríguez, Tiare Zulaima; Serna, Robinson Julián (Uptc, 2021)
This article is a review of the research and teaching activities of Manuel Suárez Martínez—1941-2020—professor emeritus of the Pedagogical and Technological University of Colombia between 1971 and 2004, who achieved national and international recognition for the quality and importance of his work in point-set topology and for his legacy in the training of mathematics teachers. Based on interviews, documents, testimonies, videos, and images, arranged and interpreted according to the guidelines of grounded theory, his main research projects, teaching strategies, and teaching experiences are described, aiming to ensure that time does not erase his invaluable contribution.